2017
DOI: 10.1186/s12902-017-0158-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality of sleep and risk for obstructive sleep apnoea in ambulant individuals with type 2 diabetes mellitus at a tertiary referral hospital in Kenya: a cross-sectional, comparative study

Abstract: BackgroundSleep disorders are common and associated with multiple metabolic and psychological derangements. Obstructive sleep apnoea (OSA) is among the most common sleep disorders and an inter-relationship between OSA, insulin resistance, obesity, type 2 diabetes (T2DM) and cardiovascular diseases has been established. Prevalence of sleep disorders in Kenyans, particularly in individuals with T2DM is unknown. We thus aimed to determine prevalence of poor quality of sleep (QOS) and high risk for OSA, among pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 32 publications
4
19
3
1
Order By: Relevance
“…We also excluded patients with poor glycemic control, restless leg syndrome, and obstructive sleep apnea that can cause sleep disruption. 50,60 Pupil size and sleep quality reduces with increasing age, particularly above 65 years, 61 and both groups were age-matched to correct for the effect of age. Moreover, the analysis of the average baseline pupil diameter showed that it was not significantly different between groups.…”
Section: Discussionmentioning
confidence: 99%
“…We also excluded patients with poor glycemic control, restless leg syndrome, and obstructive sleep apnea that can cause sleep disruption. 50,60 Pupil size and sleep quality reduces with increasing age, particularly above 65 years, 61 and both groups were age-matched to correct for the effect of age. Moreover, the analysis of the average baseline pupil diameter showed that it was not significantly different between groups.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 53.4% of diabetic patients experience a poor quality of sleep compared to 29% in general population. 8 Concerns over poor sleep quality among patients with diabetes have increased in recent years, but the implicated risk factors of poor sleep quality remain uncertain. Different factors that may affect the sleep quality of patients with diabetes have been suggested by many studies, including sociodemographic, clinical, and diabetes-related factors, such as duration of diabetes, diabetic complications, presence of comorbidity, 9 uncontrolled glycosylated hemoglobin, 10 abnormal body mass index (BMI), 11 insulin use, 12 and psychological factors.…”
Section: Introductionmentioning
confidence: 99%
“…4 OSA is strongly correlated with multiple disease conditions, including type 2 diabetes mellitus (T2DM), hyperlipidemia, hypertension, heart failure, cardiovascular diseases (CVD) and depression. 4,5…”
Section: Introductionmentioning
confidence: 99%